Modulatory Effect of Dietary Polyunsaturated Fatty Acids on Immunity, Represented by Phagocytic Activity - Al-Khalaifah, Hanan (Frontiers in Veterinary Science, 2020)
Lately, dietary polyunsaturated fatty acids (PUFAs) have shown substantial importance in human and animal nutrition, especially those of the n-3 group. Development and optimal functioning of the immune system are directed affected by diet. These dietary fatty acids have an important impact on the health and immune competence of various species including human beings. They are essential for the modulation of immune responses in health and disease. Fatty acid composition of immune cells can be modulated by the action of dietary fats and the outcomes in the composition can produce functional effects on reactivity and functioning of immune cells in a short period. There are several mechanisms involved in impacting dietary fatty acids on immune function; however, lipid mediator synthesis from PUFAs is of great importance in terms of inflammation. The objectives of this article are reviewing studies on the impact of PUFA in the diet on phagocytosis of chickens, murine, rats, ruminants, and humans. It also sheds light on the possible mechanism by which this immunomodulation occurs.